Digital Transformation of Rural Areas in the Conditions of Innovative Development of the Western Sector of the Russian Arctic - Elena N. Bogdanova; Aleksandr A. Saburov; Oleg V. Minchuk; Aleksey S. Nikiforov (Арктика и Север)
Complex natural-climatic and spatial-geographical conditions, which comprehensively characterize the Arctic as a zone of absolute discomfort, create systemic barriers to the introduction of digital technologies necessary for levelling the risks of population preservation. Of particular strategic importance for the Arctic zone of the Russian Federation are rural territories that provide a presence in the vast and sparsely populated space of the Russian Arctic, including in the areas of exploitation of key deposits of mineral and biological resources. The aim of the article is to analyze the directions of digital transformation of regional development that promotes innovative development of rural territories in the Western sector of the Russian Arctic (on the example of the Arkhangelsk Oblast and the Nenets Autonomous Okrug). Along with comparative analysis of scientific publications and content analysis of normative legal documents, a systematic review of strategic planning documents and indicators assessing the level of digitalization of the Arkhangelsk Oblast and the Nenets Autonomous Okrug with a special focus on the quality of life of the population was carried out. The analysis showed that digitalization processes react sensitively to the political and socio-economic situation, primarily the COVID-19 pandemic, economic recession and sanctions restrictions. The priorities of regional policy in the field of digital transformation have been identified, and insufficient attention to rural areas in this matter has been revealed. Under the concept of regional development “center-periphery”, the gap in the degree of development of digital ecosystems between urban and rural settlements is expected to increase, but the lack of official statistical indicators does not allow assessing its depth. Promising areas of state policy in the digital economy include systematic formation of digital competencies of the population, since digital literacy is the most important prerequisite for obtaining significant socio-economic effects of digitalization, as well as increasing the level of technical equipment of organizations, including through the expansion of subsidy programs for purchase of technical equipment used to provide goods, works and services of a socially oriented nature for the population.